2006
DOI: 10.1515/sosys-2006-0107
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Function of Forgetting: Revisiting Exploration and Exploitation in Organizational Learning

Abstract: ZusammenfassungDie computerbasierte Simulation ist zu einer weithin akzeptierten Methodik in den Sozialwissenschaften avanciert, insbesondere in der Organisationsforschung. In diesem Beitrag replizieren wir zunächst eine computerbasierte Simulation aus dem Bereich des organisationalen Lernens von James G. March. Im Anschluss daran modifizieren und erweitern wir die Replikation unter Rückgriff auf die Theorie sozialer Systeme Niklas Luhmanns. Während Marchs ursprüngliches Simulationsmodell vor allem die Konzept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…Memory typically fades over time both at the individual (Schacter, 2002) and collective (Schudson, 1995) levels. It is, in fact, forgetting, rather than remembering, that is the primary function of memory (Blaschke & Schoeneborn, 2006), given the vast number of events we encounter. Social memory studies suggest that passing time creates an emotional distance between a mnemonic community and past events.…”
Section: Collective Memory and Forgettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory typically fades over time both at the individual (Schacter, 2002) and collective (Schudson, 1995) levels. It is, in fact, forgetting, rather than remembering, that is the primary function of memory (Blaschke & Schoeneborn, 2006), given the vast number of events we encounter. Social memory studies suggest that passing time creates an emotional distance between a mnemonic community and past events.…”
Section: Collective Memory and Forgettingmentioning
confidence: 99%
“…Forgetting more than we remember is often useful. Selective forgetting can have positive consequences (Hedberg, 1981;Nystrom & Starbuck, 1984), since it helps mnemonic communities become sensitive to environmental changes and continue to evolve in response to their surroundings (Blaschke & Schoeneborn, 2006). Studies of organizational learning have similarly demonstrated that selective forgetting is crucial for sustained organizational life and continuity (Brown & Starkey, 2000;de Holan, 2011).…”
Section: Collective Memory and Forgettingmentioning
confidence: 99%
“…The costs and efforts involved in storing and copying information are low (Whelan and Teigland, 2013 ). Organizational processes such as “Exploration and Exploitation” (March, 1991 ), which describes the search, acquisition and elaboration of new information, the intensive and excessive use of information, and the evaluation of information as an important resource, have led to a continuous increase in available and recallable stored knowledge (Blaschke and Schoeneborn, 2006 ; Miller and Martignoni, 2016 ).…”
Section: Organizational Learning and The Supplemental Need For Forgetmentioning
confidence: 99%
“…Despite incorporating different assumptions about the learning mechanism and social network structure, these models all share the implicit assumption that agents never forget. Blaschke and Schoeneborn (2006) provide the sole exception. Adding forgetting produces results that differ from the established negative relation between the learning rate and long-run average knowledge (see Figure 3(a) and (b)).…”
Section: Research Implicationsmentioning
confidence: 99%